2019
DOI: 10.1038/s41596-019-0205-z
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotope labeling of metal/metal oxide nanomaterials for environmental and biological tracing

Abstract: Engineered nanomaterials are often compositionally indistinguishable from their natural counterparts and thus their tracking in the environment or within biota requires the development of appropriate labelling tools. Stable isotope labelling has become a well-established such tool, developed to assign "ownership" or "source" to engineered nanomaterial enabling their tracing and quantification, especially in complex environments. A particular methodological challenge for the stable isotope labelling is to ensur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 47 publications
(53 reference statements)
0
29
0
Order By: Relevance
“…Tracking the trace elements or metal contamination contained in the nanomaterials as a surrogate has shown some success for select materials such as carbon nanotubes and nano-scale zero-valent iron. [93,94] IStrategies such as isotopic labeling of nanomaterials such as carbon nanotubes, [95] and doping nanomaterials with low abundance rare earth metals, such as holmium (Ho) [88] Isotopic labeling still requires extraction of the nanotubes and specialized equipment for isotope detection. However, a more recent study has shown that using the doping method and spICP-MS nanoparticles can be detected at down to 1 × 10-3 ng L −1 in complex natural environments.…”
Section: Unknowns Impact Determining Fate and Distribution In The Envmentioning
confidence: 99%
“…Tracking the trace elements or metal contamination contained in the nanomaterials as a surrogate has shown some success for select materials such as carbon nanotubes and nano-scale zero-valent iron. [93,94] IStrategies such as isotopic labeling of nanomaterials such as carbon nanotubes, [95] and doping nanomaterials with low abundance rare earth metals, such as holmium (Ho) [88] Isotopic labeling still requires extraction of the nanotubes and specialized equipment for isotope detection. However, a more recent study has shown that using the doping method and spICP-MS nanoparticles can be detected at down to 1 × 10-3 ng L −1 in complex natural environments.…”
Section: Unknowns Impact Determining Fate and Distribution In The Envmentioning
confidence: 99%
“…For example, identification and quantification of transformation products in soil and plant tissues are challenging due to the presence of high background interferences in such samples. Advanced techniques such as synchrotron radiation based techniques (e.g., X-ray absorption fine structure spectroscopy) combined with imaging techniques including scanning transmission X-ray microscopy (STXM) and micro X-ray fluorescence (µ-XRF), [122] and isotope labeling approaches [49,123] coupled with in situ detection techniques such as autoradiography, [100] Nano Secondary Ion Mass Spectrometry (NanoSIMS), [124] laser ablation inductively coupled plasma mass spectrometry (ICP-MS), [125] and single particle/cell ICP-MS are all sophistical techniques that can be brought to bare for studying ENMs transformation. Metabolomics, [126] proteomics, [127] exposomics, [128] and secretomics [129] are emerging powerful tools to identify the components of root exudates, EPS, and plant/microbial metabolite response to ENMs exposure.…”
Section: Take Advantage Of the Emergence Of State Of The Art Analyticmentioning
confidence: 99%
“…Thus, it allows the detection of 65 Cu body burdens in minute tissue samples, such as from T. tubifex (a few mg), despite the high Cu background levels in their tissue. One of the many advantages of this particular labeling method is that the label is incorporated into the NP during synthesis to have a unique isotopic composition throughout (Zhang et al, 2019). This makes the label more robust and reliable than labels attached to the surface, such as fluorescent markers, which can possibly be released (Schür et al, Reproductive output is presented as the mean ± SD number of cocoons at the end of exposure and hatchability (number of cocoons hatched, 2.5 months after exposure termination).…”
Section: Exposure Characterizationmentioning
confidence: 99%
“…). An array of papers can be consulted for further discussion on the technique (Croteau et al, 2011b;Dybowska et al, 2011;Misra et al, 2012b;Zhang et al, 2019).…”
mentioning
confidence: 99%